Organisational Politics – Causes and Effects on Organisation and Employees - Eniola, Sule Olatunji; Iyabo, Amuni Sarat; Adeshina, Ashiru Titi; Olajide, Ariyo Oladayo (International Journal of Business, Economics and Management, 2015)
This work was just to look at the causes and the effects of politics within organisation. It started with the reasons for groups within organisations, causes and possible effects of organisational politics on the organisation and the employees. Finally, the work made it clear that employees need to relate which may give room for politicking but moderation and utmost supervision should be the guarding principle.